Test Results Of Quality Control Examination Of Erythrocytes (RBC), Hemoglobin (HB) And Thrombocytes (PLT) Using The Six Sigma Method At UPTD RSUD - Kristinawati, Erna; Jannah, Miftahul; Jiwantoro, Yudha Anggit (Poltekkes Kemenkes Mataram, 2025)
Hospital quality must be improved to maintain the quality of service to patients. One of the laboratory tests is hematology examination. Hematology examination has used Automatic Hematology Analyzer. To ensure the accuracy, precision and accuracy of laboratory examinations, Quality Control is needed. Six Sigma is a metric that measures process performance as the level of Defects Per Million Opportunities (DPMO), DPMO is one of the Process Capability assessments to measure how good a production process is on a scale of 1-6. To determine the quality of tools using the Six Sigma method. The research was conducted at UPTD RSUD X by taking data from Quality Control results, the data was analyzed using six sigma so that this research is a descriptive observational research and the nature of this research is Retrospective Cross-sectional. The average control results in March for low, normal, and high erythrocyte level examinations were 2.21, 4.16, and 4.91. The average control results for platelet parameters were 53.74, 266.65, and 486.97. and for hemoglobin parameters were 5.48, 11.80, and 15.22. In April, the average control results for erythrocyte parameters were 2.25, 4.19, 5.01, while the average control results for platelets were 50.07, 240.89, and 489.36. Then, the hemoglobin parameter showed an average control result of 5.56, 11.94, and 15.65. The control results for each parameter are still acceptable because based on the Westgard rules, no control results exceed 3SD